Annealing and investigation of copper oxide synthesized using coaxial magnetoplasma accelerator; Control and Communications (SIBCON) - Shanenkova Yu. L. Yuliya Leonidovna; Sivkov A. A. Aleksandr Anatolyevich; Shanenkov I. I. Ivan Igorevich; Ivashutenko A. S. Alexander Sergeevich; Nikitin D. S. Dmitry Sergeevich (2015, 2015)
Title screen